Recaudación de fondos por autogestión en la Cooperativa de Transporte Interprovincial Babahoyo - Arreaga Vera, Maricela del Rocio (2018)
Currently in Ecuador there are several cooperatives that provide rural transport service, among which is the Cooperativa de Transporte Interprovincial Babahoyo (CTIB), domiciled in the canton Babahoyo, province of Los Ríos. The contributions made by the members to this cooperative are limited and their responsibility falls on the members that comprise it. The purpose of this cooperative is to provide transport services with efficiency and responsibility by professional drivers, in exchange for an economic consideration or rate that allows the daily support of members and their families.